-4(2y-8)+4y=6(y+6)

Simple and best practice solution for -4(2y-8)+4y=6(y+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2y-8)+4y=6(y+6) equation:



-4(2y-8)+4y=6(y+6)
We move all terms to the left:
-4(2y-8)+4y-(6(y+6))=0
We add all the numbers together, and all the variables
4y-4(2y-8)-(6(y+6))=0
We multiply parentheses
4y-8y-(6(y+6))+32=0
We calculate terms in parentheses: -(6(y+6)), so:
6(y+6)
We multiply parentheses
6y+36
Back to the equation:
-(6y+36)
We add all the numbers together, and all the variables
-4y-(6y+36)+32=0
We get rid of parentheses
-4y-6y-36+32=0
We add all the numbers together, and all the variables
-10y-4=0
We move all terms containing y to the left, all other terms to the right
-10y=4
y=4/-10
y=-2/5

See similar equations:

| 14=8x/29 | | -9u+14=-5(u-2) | | 4x-26+5x+3+7x+7=180 | | 4(x-6)-6x=-4 | | 2(5x-18)=180 | | 3y+32+9y-11=180 | | 2/7a+4=-6 | | M=-5,b=2.5 | | (3/(x-2))+(4/5)=27/(5(x-2)) | | (3/(x-2))+4/5=27/(5(x-2)) | | M=7,b=1 | | 9p+4=5p+16 | | M=4,b=3.8 | | x+0.09x=65.02 | | x+.2x=750 | | 4y^2+13y-3=0 | | 8c+3(c-11)=33 | | X+21x=100 | | 81x2-1=27 | | 2(x-4)=6x-32 | | x-6.59=4.22 | | 9w^2=-18w | | 2/3(2t–7)+2/3t=-95/3–t | | ((1+i)(1+i))-2i=0 | | 58=3y+13 | | 3(-1)-2(x+3=0 | | 3(x-1)-2(x+3)=8 | | 28=x-47 | | n-6=38 | | 5+4x=-4 | | 2x-2=208 | | 3=4(x+1)-3(x+6) |

Equations solver categories